Gestational Diabetes: Physical Activity Before Pregnancy and Its Influence on the Cardiovascular System - Sitzberger, Christina; Oberhoffer-Fritz, Renate; Meyle, Kristina; Wagner, Maike; Lienert, Nadine; Graupner, Oliver; Ensenauer, Regina; Lobmaier, Silvia M.; Wacker-Gußmann, Annette (Frontiers in Pediatrics, 2020)
Objectives: Gestational diabetes mellitus (GDM) is a common complication in pregnancy, affecting around 14% of all pregnancies each year. It will likely further increase, as obesity becomes more prevalent. The impact of GDM on cardiovascular changes in pregnant women and her child is still unclear. The aim of the study was to measure the effects of physical activity before pregnancy on the cardiovascular system in patients with GDM to establish prevention programs. Methods: 206 pregnant women were included in this observational study. All participants were recruited in an obstetrical department between 28 and 32 weeks gestation. Questionnaires dealing with pre-pregnancy daily and physical activity (PA) were evaluated. The cardiovascular status of the mothers included measurements of the intima-media thickness (IMT) of the carotid arteries. Physical activity level was performed with a standardized 6-minute-walking-test. Results: 99 women with GDM with a mean age of 33.84 (SD ± 4.7) years were examined. 107 healthy pregnant women aged 32.6 (SD± 4.2) years served as controls. The mean weight in the study group was 73.0 (SD± 20.3) kg and 61.7 (SD± 9.5) kg in the control group. Based on the higher weight in the study group, the Body Mass Index (BMI) was also significantly higher than in the control group (26.3 (SD± 7.1) vs. 21.6 (SD ± 3); p=0.001). The frequency of PA was significantly higher in the control group (p = 0.001). The objective fitness level was worse in pregnant women with GDM compared to healthy controls (472 meters vs. 523 meters, p < 0.001). PA before and during pregnancy was less performed in the study group (86% vs. 64.5%, p = 0.002; 69% vs. 45.7%, p = 0.003). Women who were physically inactive before pregnancy had a 3-times higher risk to develop GDM compared to active women (OR = 3.1). The IMT (A. carotis interna) was significantly thicker in the study group (0.47 (SD± 0.004) mm vs 0.44 (SD± 0.009) mm; p=0.006).